FROM ALIENATION TO ACCEPTANCE: A MESSAGE FROM THE BUTTERFLY MOSQUE - M. Faqih Azam Majid; Defi Yulia Hardiana; Zulfi Zumala Dwi Andriani; M. Tazkiya syah (Journal of English Literature and Linguistic Studies, 2026)
AbstractThis research aims to determine the form of Wilson's life journey in the novel "The Butterfly Mosque" finds his identity in a different country in terms of race, ethnicity, and customs based on real life from alienation to receiving the message: from the butterfly mosque. To obtain this analytical data, researchers used qualitative descriptive methods. The story focuses on Wilson's experiences as an American Muslim woman trying to find a balance between her Western identity and her new Islamic life. She also shared the difficulties she faced in dealing with differences in culture and beliefs, and how she tried to understand and accept these differences in everyday life. The religious identity in question is a journey of search and acceptance, a change from doubt and confusion to confidence and peace on Wilson's journey. Moreover, Wilson provides an in-depth perspective on how someone can find an authentic religious identity despite being amidst the tension between two very different worlds. The results of the analysis show that The Butterfly Mosque is not only a story of religious conversion, but also a bridge that shows how individual experiences can transcend cultural boundaries and create space for dialogue, tolerance, and understanding between civilizations. This book is relevant for readers interested in issues of identity, globalization, and intercultural relations.